2018
DOI: 10.1016/j.evolhumbehav.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A noisy signal: To what extent are Hadza hunting reputations predictive of actual hunting skills?

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 65 publications
(103 reference statements)
1
42
1
Order By: Relevance
“…Practically, this could be achieved by assessing the relationship between the actions and traits of potential senders and receivers' perceptions and responses to them. This can be done through such techniques as reputational sorting tasks and observational studies of behavior, and ideally would involve measurement of many potential traits, actions, and reputational assessments in order to pinpoint the actual signal content . Broadly, researchers should aim to identify the payoffs of signaling for both the sender and receiver under a range of receiver responses, in order to ultimately identify signal function.…”
Section: Future Directionsmentioning
confidence: 99%
“…Practically, this could be achieved by assessing the relationship between the actions and traits of potential senders and receivers' perceptions and responses to them. This can be done through such techniques as reputational sorting tasks and observational studies of behavior, and ideally would involve measurement of many potential traits, actions, and reputational assessments in order to pinpoint the actual signal content . Broadly, researchers should aim to identify the payoffs of signaling for both the sender and receiver under a range of receiver responses, in order to ultimately identify signal function.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is also possible that hunting success is related to measures of RS due to a confounding variable. For example, strength might contribute independently to hunting success and RS …”
Section: The State Of the Evidence For Human Hunting As A Costly Signalmentioning
confidence: 99%
“…Some recent work has found a relationship between hunting reputation and upper body strength, although upper body strength may not be otherwise cryptic as it can be assessed visually . Similarly, Stibbard‐Hawkes et al found that Hadza hunting reputation predicted several hunting skills including aim, upper body strength, and an ability to recognize the vocalizations of prey species, albeit with a degree of noise, disagreement and error. If hunting is indeed an honest signal, more work must be done to show it is correlated with an otherwise cryptic but adaptively relevant quality.…”
Section: The State Of the Evidence For Human Hunting As A Costly Signalmentioning
confidence: 99%
See 2 more Smart Citations